PENGARUH COVID-19 TERHADAP PERGERAKAN NILAI TUKAR RUPIAH - Muhamad Rafi Syahiddin (2023)
Exchange rate is an important element in the global financial system that influences international trade, investments, and the economic stability of a country. The purpose of this final project is to analyze the factors that affect changes in exchange rates and their impact on the economy. The data analysis methods used include literature review and collection of secondary data. The factors analyzed include global economic factors, domestic factors, and external factors. The results of this analysis provide a better understanding of the complexity of factors that influence exchange rates and offer insights for market participants, investors, and policymakers. A deep understanding of these factors is crucial for managing risks and maximizing opportunities in international economic activities.